(untitled) (Research, Society and Development, 2022)
Nursing as a science and profession is designed to sustain life and promote biopsychosocial functions, and hospitals are one of its main workplaces. This paper aims to evaluate nursing care in the treatment of acute respiratory distress syndrome in Intensive Care Units. The study has a qualitative approach and a basic nature, this study is the result of a bibliographic survey on the theme in question. Nine articles were selected to compose the final sample, which demonstrated the assistance given and the difficulties encountered. During the Acute Respiratory Distress Syndrome there are several consequences among them the gas exchange impairment, which occurs due to ventilation-perfusion incompatibility, because it is when there is a physiological condition that results in the lung alveoli being perfused with blood, but the air supply fails to supply this perfused region causing low blood oxygen level. It is concluded from the articles used to construct this study that the nurse has difficulties inside the Intensive Care Units related to the treatment of the Respiratory Distress Syndrome.